If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 = 4l Solving -8 = 4l Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-4l' to each side of the equation. -8 + -4l = 4l + -4l Combine like terms: 4l + -4l = 0 -8 + -4l = 0 Add '8' to each side of the equation. -8 + 8 + -4l = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -4l = 0 + 8 -4l = 0 + 8 Combine like terms: 0 + 8 = 8 -4l = 8 Divide each side by '-4'. l = -2 Simplifying l = -2
| 5x-20(4-x)=120 | | 20+6x=-2x+28 | | 4x-.76=3(x-.03) | | 15x+24=8(10-3x)-2 | | 4y=-17y-4 | | 3(2x+3)=5(2x+1) | | 0.30x+.05(18-x)=.10(-16) | | -.5(x-6)+.5(x+2)=x-9 | | -3x-y=-6+7y | | 4(3x-2)=88 | | 26x-19=113-6x | | 6x^2+6x-8=0 | | -32a^6-28a^5-36a= | | 4p^2-2+9= | | a=.5bc | | 0=x^2-11x-5 | | -x+7=y | | 6(2x-3)=3(4x+4) | | 3p-18=4p-4 | | 5x+8-11x=5x-(3x+16) | | 4x-12=2x+10 | | (2x+28)+2y=60 | | (2x+14)+2y=60 | | 2x+2=.66666667x+9 | | 6t^2+5t=0 | | 2x+2=.67x+9 | | x^4+13x^3+39x^2-13x-40=0 | | 2x+2=.67+9 | | x^3-84x-160=0 | | 17x+9y=-7 | | (2x+2)=15 | | 1.2(1-x)=8.1+3.5x |